Investigation of tissue factor and other hemostatic profiles in experimental hypothyroidism - (:unkn) unknown (SPRINGER, 2006)
The influence of thyroid failure on hemostasis has been studied and is still not well understood. These patients have high risk for cardiovascular diseases because of the lipid metabolism and procoagulant agents. But the influence of thyroid failure on hemostasis is controversial. Tissue factor (TF) has an important role in the thromboembolic state. Recent experiments have demonstrated that TF-dependent activation of the coagulation cascade plays an important role in the pathophysiology of intravascular thrombus formation. The purpose of the present study was to investigate the contributions of TF, factor VII:C (FVII:C), factor XII:C (FXII:C), and fibrinogen in experimental hypothyroidism. TF was obtained from the thyroid gland and lung tissue of 10 rats following experimental hypothyroidism induced for 30 d and compared with similar tissue from 10 control rats. Significantly increased TF activities were found in hypothyroid rats. By contrast, FVII:C level was significantly decreased when compared with the control group. In this respect it is interesting to note that a hypercoagulable state due to increased thromboplastic activity may occur. Based on those results, elevated tissue factor activities (TFa) of the patients with low thyroid dysfunction may have another risk factor for cardiovascular diseases.
Keywords: tissue factor; hemostasis; factor VII : C; factor XII : C; hypothyroidism; APTT; FACTOR MESSENGER-RNA; ENDOTHELIAL-CELLS; THYROID-HORMONE; RISK-FACTOR; FACTOR-VII; EXPRESSION; FIBRINOGEN; INITIATION; ENDOTOXIN